Diode Laser Surgery as a Conservative Management of Hairy Tongue Lesion Resistance to Treatment - Nazanin Samiei; Hadi Kaseb Ghane; Reza Fekrazad (Case Reports in Dentistry)
Hairy tongue is a furry appearance on the dorsum surface of the tongue with variable colors. This lesion is due to defective shedding of filiform papillae. Various treatments are proposed for this condition like keratolytic agents, surgical procedure with a scalpel, or laser application. In this case study, we reported successful treatment of hairy tongue with a diode laser. The diode laser with wavelength 810 nm, power of 4 watts, a pulse width of 20 milliseconds, and an interval of 20 milliseconds by a 400-micron optical fiber was selected for treatment of this lesion. There was no bleeding during this minimally invasive surgery, and the patient experienced a low level of pain. Loss of taste function was completely resolved. Based on the result of this study, a diode laser can be a good alternative for minimally invasive surgical treatment of hairy tongue.